Comparison of fasciocutaneous V‐Y and rotational flaps for defect coverage of sacral pressure sores: a critical single‐centre appraisal. Issue 6 (6th March 2017) - Djedovic, Gabriel; Metzler, Julia; Morandi, Evi M; Wachter, Tanja; Kühn, Shafreena; Pierer, Gerhard; Rieger, Ulrich M
ABSTRACT: Pressure sore rates remain high in both nursing homes as well as in hospitals. Numerous surgical options are available for defect coverage in the sacral region. However, objective data is scarce as to whether a specific flap design is superior to another. Here, we aim to compare two fasciocutaneous flap designs for sacral defect coverage: the gluteal rotation flap and the gluteal V‐Y flap. All primary sacral pressure sores of grades III–IV that were being covered with gluteal fasciocutaneous rotational or V‐Y flaps between January 2008 and December 2014 at our institution were analysed. A total of 41 patients received a total of 52 flaps. Of these, 18 patients received 20 gluteal rotational flaps, and 23 patients received 32 V‐Y flaps. Both groups were comparable with regards to demographics, comorbidities and complications. Significantly more V‐Y flaps were needed to cover smaller defects. Mean length of hospital stay was significantly prolonged when surgical revision had to be carried out. Both flap designs have proven safe and reliable for defect coverage after sacral pressure sores. Gluteal rotational flaps appear to be more useful for larger defects. Both flap designs facilitate their reuse in case of pressure sore recurrence. Complication rates appear to be comparable in both designs and to the current literature.